Case Report: Dynamic overlap of melanoma, sarcoidosis, and targeted therapy for BRAF-mutant melanoma - Dar, Nakul; Gradecki, Sarah E.; Gaughan, Elizabeth M. (Frontiers in Oncology, 2023)
Targeted therapies, including BRAF and MEK inhibitors, are valuable treatment options for patients with unresectable or metastatic BRAF V600-mutant melanoma. With the improvement in survival seen with modern melanoma therapeutics, clinicians are learning the variable patterns associated with extended clinical courses. Sarcoidosis is characterized by non-caseating granulomatous inflammation of unknown etiology, often presenting with cutaneous, lung or lymph node involvement. There is a known association between sarcoidosis and melanoma and sarcoidosis is increasingly seen and described in the setting of anti-melanoma therapy. The challenge for clinicians is to differentiate between sarcoid-related and malignancy-related findings, which may follow a variable course over years. We present two cases of BRAF and MEK inhibitor-related sarcoidosis in patients with melanoma and review the literature. The dynamic nature of the clinical and radiographic findings impacted patient management and clinical decisions for years of their treatment course.